Anthropological determinants of success in young judoists - Krstulovic, S.; Sekulic, D.; Sertic, H. (Collegium Antropologicum, 2005)
There is an evident lack of experimental studies dealing with the anthropological determinants of success in judo, especially concerning young athletes. In this paper we have attempted to establish some of the anthropological factors potentially related to judo competition achievement in 15-16 year old athletes. A set of 14 anthropometric and 12 motor- endurance variables was tested on the best young judoists in Croatia (all males, N=34). All the subjects had competed on the National Championship (NC), and the criterion was defined according to their final NC achievement. Factor analysis and discriminant canonical analysis (DISCRA) were calculated separately on the motor-endurance and anthropometric status variables. DISCRA showed the successful judoists as dominant in strength and endurance status. In contrast, there were no significant differences in the anthropometric dimensions regarding any differentiation between the more and less successful athletes. Possible explanations are discussed.